Role of e-health, m-health, and telemedicine or telehealth during the COVID-19 pandemic - Mondal, Ramkrishna (International Journal Of Community Medicine And Public Health, 2025)
The COVID-19 pandemic has significantly disrupted the health system, leading to the adoption of digital technologies such as telemedicine, E-health, and M-health. These technologies offer numerous benefits, such as better resource allocation, reduced infection rates, and community support for patients. However, limited studies have been conducted on the effectiveness of E-health technologies, but they have shown potential to improve healthcare standards. The benefits of telemedicine include cost-effectiveness, the ability to expand higher-order services, and the potential to alleviate future medical doctor shortages. However, further research is needed to improve the trustworthiness of telemedicine-related outcomes. Several countries have issued guidelines for telemedicine, but these guidelines must be extended to address ethical issues and limited internet access due to a lack of telecom infrastructure. Developing countries have not seen widespread adoption of telemedicine, and governments have a crucial role to play in supporting this technology. Enacting and updating technology infrastructure and providing laws and guidelines for overcoming legal and ethical barriers are essential for overcoming these barriers. In conclusion, telemedicine, E-health, and M-health technologies have proven to be effective in addressing the challenges of the COVID-19 pandemic and will be promoting for a better healthcare in future.